Clinical Analysis of Pediatric Thyroid Cancer: A Single Medical Institution Experience of 18 Years. (December 2019) - Byeon, Hyung Kwon; Kim, Sang Bin; Oh, Hyeon Seok; Kim, Hong Kyu; Choi, In Hak; Kim, Hyunjung; Cho, Jae-Gu; Oh, Kyung Ho; Baek, Seung-Kuk; Woo, Jeong-Soo; Kwon, Soon-Young; Kim, Hoon Yub; et al.
Objective: The incidence of pediatric thyroid cancer is relatively low compared to the disease in adults. This study aims to present the data in our institution on pediatric thyroid cancer patients, with particular emphasis on the risk factors of recurrence together with treatment outcomes. Subjects and Methods: Between January 2000 and July 2018, patients <20 years who were diagnosed with thyroid carcinoma and primarily treated with surgery at a major large-volume tertiary medical center specializing in thyroid cancer were enrolled. A total of 83 patients were eligible for this study. Results: The majority of the studied patients were girls and adolescents (age ≥13 years). Papillary thyroid carcinoma (PTC) was the most common pathology (n = 74). PTC tumors >1 cm showed higher rate of lymph node metastasis and extrathyroidal extension than tumors ≤1 cm. All patients survived with nine PTC patients who displayed treatment failure. Age, tumor size, multifocality, lateral lymph node metastasis, and postoperative thyroglobulin levels were significant prognosticators for disease recurrence. Conclusion: Pediatric thyroid cancer is relatively rare and should be considered a specific disease entity with respect to the thyroid cancer in adults, since there are several distinctive characteristics.